The predictive validity of Bayley Scales of Infant and Toddler Development-III at 2 years for later general abilities: Findings from a rural, disadvantaged cohort in Pakistan. - Muneera A Rasheed; Ingrid Kvestad; Fariha Shaheen; Uzma Memon; Tor A Strand (PLOS Global Public Health, 2023)
Using data from a rural cohort in Pakistan (N = 1298), the study examined the predictive validity of the Bayley Scales of Infant and Toddler Development (BSID) 3rd edition on later tests of general abilities. The BSID III subscales (cognitive, language and motor) were administered at 2 years; general ability was assessed using the Verbal, Performance and Full-Scale score from the Wechsler Preschool and Primary Scale of Intelligence (WPPSI) III at 4 years, and the Fluid Reasoning Index (FRI) from the Wechsler Intelligence Scale for Children (WISC) V at 8 years. The combined BSID subscales explained 15% of the variation of the WPPSI III full scale, 16% of the Verbal scale, 7% of the Performance scale and 1% of the FRI. BSID III scores at 24 months should be used with caution to predict future intellectual abilities.